Desain Pengendali Sliding Mode Control Untuk Mengendalikan Posisi Hover Pada Unmanned Aerial Vehicle Quadcopter - faizal ahmad faizal; Ewi EWi Ismaredah; Dian Dian Mursyitah; Fernando Ahmad Zeqri (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
Quadcopter is a type of unmanned aerial vehicle that has 4 rotor to fly. one of the most important and fundamental flying movements of the Quadcopter is the hover movement, that is the ability to fly hovering that is affected by the roll, Pitch and yaw angle  (rotation motion). The hover movement becomes an inner loop of the quadcopter system so it is necessary to maintain the stability. The Quadcopter also has light and small construction, that is makes the Quadcopter difficult to maintain its stability. To resolving the stability problem, conducted simulated test using MATLAB software for controller design capable of maintaining the quadcopter stability hover movement. The proposed controller is Sliding Mode Control (SMC), the SMC is a well-known controller for its robustness. From the test results, shows the SMC is able to reach a set point of 0.1 radians in less than 1 second and maintains the stability of the hover movement at the set point of 0.1 radians without any errors steady state and overshoot with settling time 0.319 for roll and pitch angle then 0.445 for yaw angle. Keywords : Hover, Quadcopter, Rotation Motion , Settling time, SMC, Stability